Changing paradigms for targeted therapies against diffuse infiltrative gliomas: tackling a moving target. (3rd July 2019) - Carpenter, Candice D.; Alnahhas, Iyad; Gonzalez, Javier; Giglio, Pierre; Puduvalli, Vinay K.
ABSTRACT: Introduction : Gliomas are highly heterogeneous primary brain tumors which result in a disproportionately high degree of morbidity and mortality despite their locoregional occurrence. Advances in the understanding of the biological makeup of these malignancies have yielded a number of potential tumor-driving pathways which have been identified as rational targets for therapy. However, early trials of agents that target these pathways have uniformly failed to yield improvement in outcomes in patients with malignant gliomas. Areas covered : This review provides an overview of the most common biological features of gliomas and the strategies to target the same; in addition, the current status of immunotherapy and biological therapies are outlined and the future directions to tackle the challenges of therapy for gliomas are examined. Expert opinion : The limitations of current treatments are attributed to the inability of most of these agents to cross the blood–brain barrier and to the intrinsic heterogeneity of the tumors that result in treatment resistance. The recent emergence of immune-mediated and biological therapies and of agents that target metabolic pathways in gliomas have provided strategies that may overcome tumor heterogeneity and ongoing trials of such agents are anticipated to yield improved outcomes.